KEDUDUKAN DALEM PADA PROGRAM RUANG RUMAH INDIS SAUDAGAR BATIK LAWEYAN DI AWAL ABAD KE-20 - Hastuti, Dhian Lestari (Institut Seni Indoensia Surakarta, 2014)
This article is a result of research that discusses about the tradional position of dalêm in the homespace program of Laweyan batik merchants in the early 20th century which explain and understandthe position of dalêm as cultural artifacts. Two approaches are used to approach the systems of Javaneseculture and quadrant system which describes the nature of space as a symbol of Javanese culture.This study aims to understand the merchant community perspective of Laweyan socially marginalizedculture in the early 20th century, through the notch dalêm to their home space program. The resultsare: 1) physical form of three home Indies batik merchants Laweyan, a smart strategy in makingdesign decisions in harmony with nature, social environment, economic life, and ideals. 2) Position ofdalêm for the space program is regarded as a sacred area and the cosmic center, although without theapplication of the concept mancapat. Dalêm placement on the highest floor level is a reflection of thesacred area and the cosmic center. Prerequisite relations relatives and well known to the owner of thehouse is a symbol that dalêm position as a sacred area of the quadrant system.Keywords: dalêm, Indis, quadrant system, a sacred area